Argument structure effects in action verb naming in static and dynamic conditions - den Ouden, Dirk-Bart; Fix, Steve; Parrish, Todd B.; Thompson, Cynthia K. (Journal of neurolinguistics, 2009)
Argument structure, as in the participant roles entailed within the lexical representation of verbs, affects verb processing. Recent neuroimaging studies show that when verbs are heard or read, the posterior temporoparietal region shows increased activation for verbs with greater versus lesser argument structure complexity, usually bilaterally. In addition, patients with agrammatic aphasia show verb production deficits, graded based on argument structure complexity. In the present study, we used fMRI to examine the neural correlates of verb production in overt action naming conditions. In addition, we tested the differential effects of naming when verbs were presented dynamically in video segments versus statically in line drawings. Results showed increased neuronal activity associated with production of transitive as compared to intransitive verbs not only in posterior regions, but also in left inferior frontal cortex. We also found significantly greater activation for transitive versus intransitive action naming for videos compared to pictures in the right inferior and superior parietal cortices, areas associated with object manipulation. These findings indicate that verbs with greater argument structure density engender graded activation of both anterior and posterior portions of the language network and support verb naming deficit patterns reported in lesion studies. In addition, the similar findings derived under video and static picture naming conditions provide validity for using videos in neuroimaging studies, which are more naturalistic and perhaps ecologically valid than using static pictures to investigate action naming.